Czech Republic : Assessment of the SME Policy Mix - World Bank Group (World Bank, Washington, DC, 2019)
This report provides an assessment of the policies devoted to supporting small and medium enterprises (SMEs) in the Czech Republic. It presents an original analysis of all national-level SME-related policy instruments, totaling 93 instruments operational from 2013 to 2017 and disbursing 108.5 billion CZK (4.71 billion USD), using an analytical framework that compares the SME policy mix to the country needs (see Annex 1 for framework and methodology). The analysis integrates three interrelated segments: 1) A country needs assessment to determine the national needs for SME policies. The needs assessment included a macro-level analysis of the Czech Republic's performance in productivity and trade; an analysis of national- and firm-level innovation performance; a firm-level analysis of productivity across firm sizes, sectors, and regions (leveraging original data from the Czech statistics office); and an analysis of market and institutional conditions that influence resource allocation and firm productivity. 2) A policy mix analysis to determine if the Czech Republic's SME policy mix matches the needs identified in the country needs assessment. The policy mix analysis included a review of relevant SME policy stakeholders, institutions, and governance; a review of national-level strategies; identification of the characteristics of SME policies instruments (administering agency, mechanism of support, beneficiaries, etc).; and a cluster analysis to evaluate the internal consistency of the policy mix and identify overlaps. 3) Recommended areas for policy action were developed using the needs assessment and policy mix analysis to improve the effectiveness of the policy mix and the business environment.